SMALL SCALE FISHERIES AND CRUSTASEAN RESOURCES LINKAGES IN NORTH MADURA WATERS: SOCIAL-ECOLOGICAL CONNECTIVITY STUDIES - M. Nur Arkham; Arif Trihandoyo; Agus Ramli (COJ (Coastal and Ocean Journal), 2018)
Crustaceans is a fishery resource that has high economic value, where a lot of demand for exports from crustacean group. Small-scale fisheries have become the foundation for the fishermen who live in coastal areas. The purpose of this study is to identify the resource utilization of crustaceans by small-scale fisheries in North Madura Waters, and assess dependency on the existence of small-scale fisheries resources existing crustaceans in North Madura Waters. The research method is direct observation, interviews, and free dialogue with some of the respondents. The results that have been obtained from this study, so it can be concluded that small-scale fishermen who make arrests crustacean resources in North Madura Waters is fishing with fish traps and fishing gear dogol that land their catch in PPI Kranji, Sampang PPI and PPI Tamberu. Dominant Commodities catch is crabs, tiger shrimp and white shrimp. The results of the small-scale fisheries dependence on resources from the index dependence crustaceans seen mention that fishermen who landed the catch in PPI Kranji, Sampang PPI and PPI Tamberu have a resource dependency with crustaceans with an index value of 21.74; 13.87; and 0.42. Keywords: crustacea, small scale fisheries, dipandance crustacea index, North Madura Waters